2008
DOI: 10.1007/s10096-007-0452-8
|View full text |Cite
|
Sign up to set email alerts
|

Repeated enzyme immunoassays have limited utility in diagnosing Clostridium difficile

Abstract: Many clinical laboratories use enzyme immunoassays (EIA) to diagnose Clostridium difficile-associated disease (CDAD). Clinicians frequently order three EIAs to "rule out" CDAD. We performed a retrospective cohort study to determine the clinical utility of repeating EIA testing to diagnose CDAD. We reviewed all EIAs performed by our laboratory during 2005, determined the total number of tests per patient and per testing episode, and calculated the relative negative predictive value (NPV) of one EIA compared to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…and Drees et al. [55,56]. However, in an epidemic setting, NPVs of these tests will be significantly lower due to the higher prevalence of disease.…”
Section: Discussionmentioning
confidence: 99%
“…and Drees et al. [55,56]. However, in an epidemic setting, NPVs of these tests will be significantly lower due to the higher prevalence of disease.…”
Section: Discussionmentioning
confidence: 99%
“…When a positive test result is obtained on initial testing, it can only be reported as provisionally positive, and further testing must be performed with, for example, a toxin detection test [1,11]. Another potential benefit of a two‐step approach to CDI diagnosis is that it discourages the submission of multiple faecal samples for repeat testing, which studies have shown can lead to a significant increase in the number of false‐positive test results, as well as being highly wasteful of resources [16,17].…”
Section: Laboratory Diagnosis Of Cdi—still In a State Of Fluxmentioning
confidence: 99%
“…However, recent papers [7,[11][12][13][14][15][16] have suggested that repeat testing should be avoided. Drees et al [12] investigated the three sample rule using EIA testing. They reported that 85% of patients were diagnosed on the first test and attributed the improvement of the Aronnson et al results [20] to newer generation EIAs.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, many clinicians order repeat stool sample testing following a negative result, in an attempt to increase the diagnostic yield. Frequently, up to three EIAs are ordered to 'rule out' CDI [12]. Previous guidelines did not specify the optimal number of tests in the diagnostic workup of CDI [11,13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation